2019
DOI: 10.1186/s13071-019-3665-7
|View full text |Cite
|
Sign up to set email alerts
|

How sensitive and specific is the visual diagnosis of sarcoptic mange in free-ranging Iberian ibexes?

Abstract: Background Sarcoptic mange is a broadly distributed parasitic disease caused by Sarcoptes scabiei that affects wild mammals from all over the world, including the Iberian ibex ( Capra pyrenaica ). Selective culling of the scabietic individuals is the main management measure for disease control in Iberian ibex populations. Although visual identification of mange-compatible lesions is the reference method to decide the target individual, both fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…We used the same transects but only evaluated individuals within 200 m from the transect after several trials in which we established that this was the most conservative distance at which we could confidently identify infected animals with the available telescope [42]. Notwithstanding, because incipient infections are undetectable without laboratory diagnosis which require diagnostic specimens, our visual estimates represent the minimum infected proportion [43].…”
Section: Population Density and Proportion Of Living Wild Camelids In...mentioning
confidence: 99%
“…We used the same transects but only evaluated individuals within 200 m from the transect after several trials in which we established that this was the most conservative distance at which we could confidently identify infected animals with the available telescope [42]. Notwithstanding, because incipient infections are undetectable without laboratory diagnosis which require diagnostic specimens, our visual estimates represent the minimum infected proportion [43].…”
Section: Population Density and Proportion Of Living Wild Camelids In...mentioning
confidence: 99%
“…lice infestation or dermatophilosis) or conditions such as moulting. While the sensitivity of visual diagnosis high (87%), the specificity is low (61%; Valldeperes et al 2019), and both sensitivity and specificity are affected by factors such as age, sex, and time of year. Due to these limitations, the combination of visual diagnosis with the detection of mites and their eggs in skin scrapings or in skin digested with potassium hydroxide is considered the gold standard method (Valldeperes et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, ticks collected from sympatric Red deer near the study area have been recently demonstrated to harbor pathogens such as Coxiella burnetii, Babesia ovis, Borrelia burgdorferi and the Crimean-Congo Hemorrhagic Fever virus (Estrada-Peña et al 2012). Despite no cases of infestation by Sarcoptes scabiei mites were detected, a serological analysis to discard possible contact with the parasite would have been desirable; currently no standardized assay for wild ruminants is available (Valldeperes et al 2019).…”
Section: Resultsmentioning
confidence: 99%